The Application of Crisis Counseling in Shaping the Adolescent Self-Concept of the Family Broken Home - Asti Haryati; Usta Andani; Hefika Juipa Beta; Marisa Anggarini (JURNAL ILMIAH SYI'AR, 2021)
This paper aims to find out and provide information about adolescents' self-concept in broken home families. This type of research is qualitative research. The approach used in this study uses a descriptive qualitative method. This study indicates that the research subjects have a process of self-acceptance with their family conditions being different, but leading to a positive self-concept. The process of accepting the shape of the broken home family is influenced by the life of the subject who can adapt to his environment, begins to open up such as receiving input from others, and assumes that he has the same rights, namely improving his quality and abilities. Then in the aspect of self-concept dimensions, the whole subject develops knowledge of oneself, expectations, and acceptance (judgment) about oneself